Therapeutic Potential of Autologous Adipose Derived Mesenchymal Stem Cells in Human POI and Ovarian Aging - Luján, Irastorza Jesús Estuardo; Durand, Montaño Carlos; Hernández, Ramos Roberto; Ávila, Pérez Felipe de Jesús; Guerrero, Vargas José Juan; Kava, Braverman Alejandro; Ávila, Rebollar Daniela; Pariente, Fernández Maruxa; Paredes, Núñez María Angélica; Gabriel, de la Rosa Ruiz; Vargas, Hernández Víctor Manuel (Journal of Evolving Stem Cell Research, 2021)
Background Women play an important role in the work setting. This leads them to put off their motherhood, sometimes preventing them from getting pregnant. Delaying pregnancy face women with low ovarian response, such as in Premature Ovarian Insufficiency (POI) or Ovarian Aging (OA). There is no current treatment, although there is evidence of improving ovarian function by inyecting mesenchymal stem cells (MSC). Materials and Methods Prospective, observational study of 17 women who attended Pronatal Clinic from 2019 to 2020. Each patient was registered in Assisted Reproductive Treatment (ART) and was enrolled in ovarian treatment with an autologous adipose tissue Mesenchymal Stem Cell (AD-MSCs) protocol. Three groups were assembled: 1) Control: AMH >1.2 ng/mL, without AD-MSCs, 2) POI/OA: female infertility due to POI/OA with AMH <1.2 ng/mL and 3) Amenorrhea: female infertility due to POI/OA with amenorrhea and AMH <1.2 ng/mL. Variables: Age, weight, height, serum AMH, endometrial thickness, follicular size and number on day 2 and 11 of the menstrual cycle, oocyte number, number of blastocysts and pregnancy rate. Results Between month 2 and 5, after AD-MSCs inyection, POI/OA group showed an increase in follicle number (2 to 9) and size (13.5 to 15.5 mm) on day 11 of the menstrual cycle, which resulted in a higher number of MII oocytes (2.6 to 4.2), and an increase in number of blastocysts (0 to 3) and endometrial thickness (8.6 to 9.4). Regarding the Amenorrhea group, a reboot in menstrual cycle was observed, although no further development of blastocyst was found. Conclusion The AD-MSCs inyection directly in the ovary allowed an increase in number of blastocysts and improved pregnancy rates in POI/OA patients.
Keywords: Premature ovarian insufficiency; ovarian aging; Adipose-Derived Mesenchymal Stem Cells; Blastocyst